Pengaruh Influencer di Instagram terhadap Brand Awareness dan Dampaknya terhadap Purchase Intention Pada Brand Somethinc - Wicaksono, Satrio Kris; Susan, Marcellia (Jurnal Informatika Ekonomi Bisnis, 2024)
This study aims to determine the influence of influencers on Instagram on brand awareness and purchase intention for the Somethinc brand. Instagram is one of the biggest platforms for brands to communicate their products. Influencers are one of the bridges for brands to communicate the products that will be released. The results of the analysis that has been tested show that influencers have a positive and significant effect on brand awareness and purchase intention. It’s important for brands to utilize influencers to increase their market reach and have a significant effect on Instagram.